Parental Incarceration and Child Wellbeing: Implications for Urban Families - Amanda Geller
Using a population-based, longitudinal family survey (N=4,898), we identify a set of economic, residential, and developmental risks particular to the children of incarcerated parents. We use parental reports of incarceration history, demographic background, and a rich set of child and family outcomes, in a series of multivariate regression models. Children of incarerated parents face more economic and residential stability than their counterparts. Children of incarcerated fathers also display more behavior problems, though other developmental differences are insignificant. Several family differences are magnified when both parents have been incarcerated. We find that incarceration identifies families facing severe and unique hardship. Given the prevalence of incarceration, this means a large population of children suffers unmet material needs, residential instability, and behavior problems. These risks may be best addressed by using the point of incarceration as an opportunity for intervention, and the administration of age-appropriate social services.